Effect of Sexed Semen on Dairy Heifer Supply from 2006 to 2012 - Albert de Vries (EDIS)
AN242, a 7-page illustrated fact sheet by Albert De Vries, describes the estimated impact of the use of sexed semen on the national dairy heifer supply. Includes references. Published by the UF Department of Animal Sciences, May 2010.